2018
DOI: 10.15789/1563-0625-2018-6-847-854
|View full text |Cite
|
Sign up to set email alerts
|

DIFFERENTIATED EFFECTS OF GLUCOSAMINYLMURAMILDIPEPTIDE ON THE NONTRANSFORMED AND EXPERIMENTALLY TRANSFORMED PHENOTYPE OF CD62L+CD63+CD66d+ NEUTROPHILIC GRANULOCYTES IN CONVENTIONALLY HEALTHY PEOPLE

Abstract: Modern studies have shown a high plasticity and phenotypic diversity of neutrophilic granulocytes (NG) provided by different receptors, which are diagnostic markers for the functional capacity of the cell in the course of their activities. We investigated NG from peripheral  blood, obtained from healthy people of both sexes aged from 26 to 66 years. Evaluation of the neutrophil membrane receptor expression was carried out by flow cytometry. The relative amount of neutrophilic granulocytes expressing membrane C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Muramyl peptides change the phenotype and functional activity of neutrophil granulocytes [107][108][109] and natural killer cells (NK cells) [110,111], and activate Th17 [112] and regulatory T cells (Tregs) in response to influenza virus infection [113]. Depending on the microenvironment, MPs polarize the immune response towards Th1 or Th2 [114,115].…”
Section: Muramyl Peptide Regulation Of Intracellular Signaling Pathwaysmentioning
confidence: 99%
“…Muramyl peptides change the phenotype and functional activity of neutrophil granulocytes [107][108][109] and natural killer cells (NK cells) [110,111], and activate Th17 [112] and regulatory T cells (Tregs) in response to influenza virus infection [113]. Depending on the microenvironment, MPs polarize the immune response towards Th1 or Th2 [114,115].…”
Section: Muramyl Peptide Regulation Of Intracellular Signaling Pathwaysmentioning
confidence: 99%
“…Numerous studies indicate a significant phenoty pic and functional NG heterogeneity [2,4,7,9] as well as existance of diverse subsets. NGs are incredibly plastic cells able to reshape their phenotype under microenvironmental influence and change their properties.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is shown that altered normal functioning of neutrophil granulocytes, both quantitatively and qualitatively, exerts negative effect on the course of purulent bacterial infection, and contributes to occurrence of atypical disease course. The vector effect of immunotropic therapy on a specific NG subset may allow to correct NG dysfunctions without compromising host protection, including strategies to enhance, inhibit, or restore their functions [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation